2012
DOI: 10.1387/ijdb.113384ps
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal distribution of motility and cell fate in Dictyostelium discoideum

Abstract: Pre-starvation amoebae of Dictyostelium discoideum exhibit random movements. Starved cells aggregate by directed movements (chemotaxis) towards cyclic AMP and differentiate into live spores or dead stalk cells. Many differences between presumptive spore and stalk cells precede differentiation. We have examined whether cell motility-related factors are also among them. Cell speeds and localisation of motility-related signalling molecules were monitored by live cell imaging and immunostaining (a) in nutrient med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…There are also effects on cell motility. First, bacterially grown cells move faster than axenic cells in random motility assays [28-30]. Indeed, our own measurements show that bacterially grown JH10 and rasG-/rasC- cells migrate at higher velocities than their axenically grown counterparts during folate chemotaxis (Additional file 1: Figure S1).…”
Section: Resultsmentioning
confidence: 95%
“…There are also effects on cell motility. First, bacterially grown cells move faster than axenic cells in random motility assays [28-30]. Indeed, our own measurements show that bacterially grown JH10 and rasG-/rasC- cells migrate at higher velocities than their axenically grown counterparts during folate chemotaxis (Additional file 1: Figure S1).…”
Section: Resultsmentioning
confidence: 95%
“…Concisely, several workers have proven that when cells grown at two different nutritional conditions, are reconstituted and finally allowed to enter the developmental cycle, there appears a clear distinction in the spatial distribution of these cells in the morphogenetic structures. For instance, when cells grown in glucose fortified medium were mixed with those cells grown in the medium lacking glucose and allowed forming fruiting bodies; chiefly, those cells grown in glucose fortified medium occupied the spore mass, whereas the stalk was made from those cells grown in medium lacking glucose (Leach et al, 1973;Thompson and Kay, 2000;Sistla et al, 2012). Based on this observation, we speculated a difference in glucose reserves between the haploids and diploids, as the diploids are double the size of haploids.…”
Section: Discussionmentioning
confidence: 99%
“…Both calcium concentration (Azhar, Manogaran, et al, 1996) and pH (Van Duijn and Inouye, 1991) differences, moreover, can result in heterogeneity in cell motility, which is also known to vary with the phase of the cell cycle (Walmod et al, 2004). Analysis of a handful of trajectories suggests that, corresponding to bimodality in calcium concentration at the onset of development (Azhar, Manogaran, et al, 1996), also cell motility could be bimodally distributed (Goury-Sistla et al, 2012). Already in 1957 John Tyler Bonner suggested that faster cells would position themselves to the front of the slug, thus becoming stalk with a higher probability (Bonner, 1957).…”
Section: Cell Phenotype Through Developmentmentioning
confidence: 99%